Map showing the overland and overseas flights of Charles A. Lindbergh - Clegg, Ernest (John Day Company, 1928)
Scale approximately 1:13,000,000 Scale approximately 1:13,000,000. Equatorial scale of nautical miles. Covers from Norway west to Alaska and from Brazil north to Greenland. Includes text and color illustrations. Accompanied by storage folder, constructed of paper, 32 x 38 cm.